Ejercicios de Kegel en el tratamiento post prostatectomía - Patricia del Rocío, Yánez Bustos (2021)
Abstract This research work was of a documental type and the objective that was proposed was to investigate the efficacy of Kegel exercises in the treatment of post-prostatectomy patients through the bibliographic search, to expand the scientific, comprehensive and specific knowledge, delving into the definitions of Prostatectomy, Kegel exercises and their importance in the treatment of post-prostatectomy patients. Through the exhaustive search of documents, books, scientific articles, doctoral theses, abstracts found in different databases, mostly Scielo, but it was also found in Dialnet, Scopus, Science Direct, taking into account research works that are not older than 5 years so that the information is more current and the type of studies was not restricted, in most cases the full articles were examined and those that were not considered relevant were discarded, several of the authors who are immersed in this document are: (Altamirano K., 2017), (Crespo, 2019), (Garcés, 2019), (Eroles, 2018), (León, 2016), (León, 2016), (Noa & Vila, 2020), (Randall, 2020), among others. On the other hand, the articles that obtained a rating greater than 5 were included in the bibliographic review, a total of 35 studies with reliable results. It was concluded that Kegel exercises are the easiest and scientifically proven treatment that effectively changes the quality of life of post-prostatectomy patients, strengthening the pelvic floor muscles and controlling urinary incontinence, these results are presented after analyzing the selection of documents intended for this research that is a contribution to other similar or larger studies. Keywords: Kegel exercises, prostatectomy, physiotherapeutic treatment. Reviewed by: Mgs. Geovanny Armas Pesántez ENGLISH PROFESSOR C.C. 0602773301